Development of a Clinical Nursing Practice Guideline for the Acute ST Elevation Myocardial Infarction Patients in Emergency Department, Songklanagarind Hospital - Senuphai, Wannipha; Te-chato, Panida; Damnoi, Siriporn (Princess of Naradhiwas University Journal, 2019)
This study aims to develop a Clinical Nursing Practice Guideline (CNPG), for the Acute ST-Elevation Myocardial Infarction (STEMI) patients, and to study the use of CNPG for the STEMI patients at the Emergency Department of Songklanagarind Hospital. Application of the Iowa model, as evidence-based practice for promotion quality of care, was utilized as the concept guideline in developmental protocols. The protocols are comprised of eight steps.This practice was developed from 9 evidence-based-articles,under the supervision of5persons. Twenty ninenurses were assigned to practice with 25 target patients, The outcomes or results evaluated according to the CNPG found that the practices were carried out in all practice guidelines (100%). When the patients arrived at the emergency department they receivedelectrocardiographic (EKG) within an average of 6 minutes and Percutaneous Coronary Intervention (PCI) within 90 minutes (96%). As to the nurse’s opinions,these practice guidelines could be really used for patient care at the highest score of 4.34 (standard deviation 0.48). The results from this study suggest that it is necessary to evaluate the propriety context of each hospitalfor further efficiency practice of nurses.